Phenotypic Variability with SLURP1 Mutations and Diffuse Palmoplantar Keratoderma - Liisa Harjama; Kaisa Kettunen; Outi Elomaa; Elisabet Einarsdottir; Hannele Heikkilä; Sirpa Kivirikko; Katriina Lappalainen; Janna Saarela; Caroline Alby; Annamari Ranki; Juha Kere; Smail Hadj-Rabia; et al. (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)